(untitled) (UNED Research Journal, 2017)
Wastewater treatment aims to ensure that the effluents from domestic and industrial processes are disposed without endangering human health and with the least possible effect on the environment. In Costa Rica, the sewerage system covers only a part of the population (less than 25 %), so that many households, industries, as well as public and private institutions, have their own treatment systems. In this work, we evaluated the efficiency of the wastewater treatment plant at the Universidad de Costa Rica, Sede de Occidente campus (PTAR-SO). This mostly due to an increasing concern that PTAR-SO was not complying with the parameters established by the Costa Rican legislation and it might be polluting the Quebrada El Estero in San Ramón, Costa Rica. For this purpose, effluent quality monitoring was carried out during a period of 12 months. It measured the nine universal parameters for wastewater: Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Fats and Oils (FyO), Potential Hydrogen (pH), Sedimentary Solids (S. sed), Active Substances to Methylene Blue (ASMB), temperature (C°), Total Suspended Solids (TSS) and flow (Q). The laboratory results obtained suggests that PTAR-SO wastewater treatment plant operates and complies with the parameters allowed by the binding legislation. Also, when PTAR-SO parameters were compared to those obtained by a more modern treatment plant with maintenance and operation adapting, no significant differences were found among them, with the exception of S. sed and C°. Therefore, we can conclude that PTAR-SO complies with the parameters established in the national legislation and its effluents are not significantly harming any ecosystem nor the health of people.